Effects of grapeseed extract on doxorubicin-induced cardiotoxicity in rats - Adiyaman, Mehmet Sahin; Adiyaman, Ozlem Aba; Dagli, Adile Ferda; Karahan, Mehmet Zulkif; Kaya, Ilyas; Dagli, Mustafa Necati (Urban & Vogel, 2021)
Background Doxorubicin (DX) is used for the treatment of many types of cancer; however, a side effect of this agent is cardiotoxicity, which may lead to cardiomyopathy or cardiac failure. Oxidative stress is thought to play a major role in the development of cardiotoxic effects. Proanthocyanidins found in grapeseed (GS) extract may inhibit chemically induced lipid peroxidation and apoptosis caused by oxidative stress. We aimed to investigate the cardioprotective effects of GS extract against DX-induced cardiotoxicity. Methods A total of 28 male Sprague Dawley rats were grouped to receive: (a) standard nutrition (n= 7); (b) standard nutrition with an additional dose of 10mg/kg DX (n= 7); (c) standard nutrition plus 100mg/kg/day of GS (n= 7); (d) standard nutrition with 100mg/kg/day of GS plus a single dose of 10mg/kg DX. After 35 days the rats were decapitated and blood samples were taken for biochemical testing. Cardiac tissue samples were prepared for microscopy and histopathological evaluation. Results Rats in the DX group exhibited significant elevations in biomarkers such as troponin and NT-proBNP as well as in oxidative stress markers compared with all other groups. Histopathological examination corroborated these findings by demonstrating significant and severe structural injury in the cardiac tissue of DX rates. Moreover, rats in the DX+ GS group had significantly lower cardiac injury than rats in the DX group according to both biochemical (troponin and NT-proBNP) and histopathological analyses. Serum malondialdehyde levels (a marker of oxidative stress) in the DX+ GS rats were significantly lower than in the DX rats. Conclusion Our findings suggest that GS may reduce the severity of DX-induced cardiotoxicity and thus has the potential to prevent cardiac injury in this setting.
Wirkung von Traubenkernöl-Extrakt auf doxorubicininduzierte Kardiotoxizität bei Ratten
Keywords: Proanthocyanidins; Anthracycline; Oxidative stress; Cardiotoxic agents; Cardioprotective agents